The archaeal class Halobacteria and astrobiology: Knowledge gaps and research opportunities - Wu, Jia-Hui; McGenity, Terry J.; Rettberg, Petra; Simões, Marta F.; Li, Wen-Jun; Antunes, André (Frontiers in Microbiology, 2022)
Water bodies on Mars and the icy moons of the outer solar system are now recognized as likely being associated with high levels of salt. Therefore, the study of high salinity environments and their inhabitants has become increasingly relevant for Astrobiology. Members of the archaeal class Halobacteria are the most successful microbial group living in hypersaline conditions and are recognized as key model organisms for exposure experiments. Despite this, data for the class is uneven across taxa and widely dispersed across the literature, which has made it difficult to properly assess the potential for species of Halobacteria to survive under the polyextreme conditions found beyond Earth. Here we provide an overview of published data on astrobiology-linked exposure experiments performed with members of the Halobacteria, identifying clear knowledge gaps and research opportunities.